IMPROVING STUDENTS’ SPEAKING SKILL THROUGH DEBATE TECHNIQUE - Sugdiyona Turgunboeva (Лучшие интеллектуальные исследования, 2024)
Abstract: This article investigates the role of a debate in language learning and teaching process and the several ways in which debate assists to excel the speaking ability. The article highlights the debate technique's noteworthy advantages, which include vocabulary growth, fluency development, the development of critical thinking and argumentation abilities, exposure to a variety of viewpoints, and the promotion of higher levels of enthusiasm and engagement. The study does, however, also recognize some possible disadvantages, including increased anxiety, a propensity to value persuasion above linguistic accuracy, less possibilities for engaging discourse, and a higher likelihood of misconceptions because debates are competitive in character.